Principles of Good Governance on Performance - Jamaluddin (Seumike : Society Progress Journal, 2025)
Good governance is widely regarded as a fundamental component in achieving organizational performance and sustainable development. This study explores the principles of good governance and their impact on organizational performance, particularly in public and private sectors. By utilizing a mixed-method approach, we analyze how transparency, accountability, participation, and rule of law influence efficiency and effectiveness. The results highlight significant positive relationships between good governance practices and performance outcomes, providing insights for policymakers and organizational leaders.